Assessing the impact of procurement practice on organizational performance - Yonas Mebrate; Kahsu Shumet (Cogent Business & Management, 2024)
Research on public procurement has attracted increased attention in recent years. Although public procurement practices have been studied in developed and developing countries, there has been little information about public procurement practices in Ethiopia. This study conceptualized and developed dimensions of procurement practice and tested the relationships between procurement practices and organizational performance. The relationships proposed in the framework were tested using structural equation modeling. The findings indicated that procurement planning and staff competency have a positive impact on organizational performance. Public institutions, particularly Universities are encouraged to apply and embark on procurement planning and staff competency practices to maximize performance. The paper concludes with some managerial implications, limitations and opportunities of the study, and suggestions for future work.
Keywords: 650; Procurement practice; procurement planning; staff competency; organizational performance; structural equation modeling